Analysis of the structure of organization of methodological work in the pedagogic professional school (Pedagogy of Higher and Secondary Education, 2013)
Maidanenko S. V. Analysis of the structure of organization of methodological work in the pedagogic professional schoolThe article highlighted the internal and external organisation of methodical work in the pedagogic professional school. Author specifies the levels of the internal organization of methodical work.
Keywords: internal organization; foreign organization; the overall structure; levels of internal structure